Kinerja Kepolisian Resor Deli Serdang Dalam Penyelidikan dan Penyidikan Tindak Pidana Korupsi - Faisal Rahmat Husein Simatupang; Alvi Syahrin; Mahmud Mulyadi; Suhaidi Suhaidi (USU LAW JOURNAL, 2019)
Abstract. In the context of eradicating criminal acts of corruption, the government has made the Indonesian Republic Law, Number 31 of 1999, which has already been changed to the Indonesian Republic Law, Number 20 of 2001 concerning Eradication of Criminal Acts of Corruption. The law referred to was born based on the consideration that the criminal acts of corruption that have been widespread all this time do not only harm the state finances but also violate social rights and the economy of the community at large; thus, the criminal acts of corruption need to be classifiedas a crime whose eradication must be done extraordinarily. The low performance of law enforcer including the police in the eradication of the criminal acts of corruption is said to be in the background underlying the birth of the Indonesian Republic Law, Number 30 of 2002 concerning the Commission of the Eradication of the Criminal Acts of Corruption (then it is said as Law of KPK (Commission of Eradication of Corruption)). The problems in this research are concerned with the Policy of Criminal Law against the Eradication of Criminal Acts of Corruption, the Position of the Police in Conducting Investigationand inquiry of the Criminal Acts of Corruption in Statutory Provisions, and the Police Performance of Deli Serdang Resor in the Investigation and inquiry of the Criminal Acts of Corruption. The type of the research conducted is the normative juridical research, that is, the research which is focused to review the application of positive principles or legal norms. The nature of analytical descriptive research constitutes the research that describes, examines, explains, and analyzes a legal rule. The results of the research show that there is a strong commitment from the government through the policy of criminal law to prevent and eradicate the criminal acts of corruption, the police are authorized to conduct the investigation and inquiry of the criminal acts of corruption in the statutory perspective in the Country of the Republic of Indonesia, and the performance of the investigation of the criminal acts of corruption done by the Police of Deli Serdang Resor is still very low. Some efforts to improve the performance of the police of Deli Serdang Resor in the investigation and inquiry of the criminal acts of corruption are the need for law enforcement fairly and consistently in accordance with legislation and other norms that apply, the need to increase the cooperation between the police, prosecutors and corruption eradication commissions substantively, structurally and the achievements which are detailed and structured, the need to increase the quality and quantity of Human Resources of the investigators of the unit of the Criminal Acts of Corruption of the Police of Deli Serdang Resor, and the need to review the article 385 of the regional government law.   Keywords: police performance, investigation, criminal acts of corruption.